KEBIJAKAN PROFESI GURU MADRASAH MELALUI PROGRAM SERTIFIKASI DALAM MENINGKATKAN KUALITAS PENDIDIKAN ISLAM - Sigit Tri Utomo (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2019)
Educators are human resources who contribute in the exploration of students at an educational institution. In general, educators should have four competencies such as professional competence, paedagogik competence, personality competence, and social competence.As an educator who has the task of developing the potential of learners, it is clear that a teacher should improve his ability with various efforts, including by writing, discussing, following scientific activities, following seminars, and other activities that are able to hone his noble duty as an educator. Because some competencies to be developed are social competence, competence, pedagogy, and professional competence. A good teacher is those who meet the requirements of professional skills either as educators. Herein lies the importance of teachers' professional quality standards to ensure the quality of teaching and learning process.In addition to being a professional educator, with the certification of teachers is expected to be an economically prosperous educator. In addition to the economic welfare it will obviously increase the motivation of teachers to develop their professional tasks through several activities such as delegation of subject teachers work (MGMP), KKG, seminars, discussion activities and even motivation to continue higher education. Because of the cost of functional allowance to teachers who have passed a certified teacher can really focus on the task of becoming an educator in an effort to educate the nation by no longer thinking about the family economy that has been the burden of teachers in Indonesia. Because we know there are still many teachers who are still far from welfare. Many who have a double profession other than to be a teacher like a buyer of used goods, public transportation drivers, newspaper delivery, fried sellers, and so forth. So ultimately the dignity of a teacher can occupy at the highest social stratification through this certification program.                   Methods of data collection in this study using literature study. In this stage, the researchers try to select the data (books) that have relevance to the professional policy of madrasah teachers through certification program in improving the quality of Islamic education. Then the authors also use the synthesis analysis that is by handling of certain scientific objects by combining the understanding of one with another understanding, which ultimately can be obtained by the new knowledge of professional policy of madrasah teachers through certification program in improving the quality of Islamic education. The author also uses content analysis that is research conducted on the information documented in the recording, good pictures, sounds, writings and others.                    With this method will be done data analysis and processing scientifically about the content of writing policy of the profession of madrasah teachers through certification program in improving the quality of Islamic education research results indicate that the government certification to teachers intended as an effort to project teachers into educators who are actually able to do their duties with good and professional who have a predetermined standard of competence. Specifically, the objectives of teacher certification are: To improve the competence of madrasah teachers in their field of knowledge, to strengthen the teaching ability of madrasah teachers, to develop madrasah teacher competence holistically so as to be able to act professionally and improve the ability of Madrasah teachers in scientific research and activity activities, information communication technology for learning purposes Keywords: Profession Policy of Madrasah Teachers, Certification, Quality of Islamic Education